DESAIN PENGEMBANGAN JARINGAN PERPIPAAN IPAL KOTA JAMBI DI KELURAHAN TALANG BANJAR, KECAMATAN JAMBI TIMUR - Ramadhani, Silfa Nabila Aldania; Ilfan, Freddy; Putra, Tri Syukria (Al-Ard: Jurnal Teknik Lingkungan, 2026)
Population growth in Jambi City may increase domestic wastewater discharge and pollute the environment if not treated properly. The Jambi City Wastewater Treatment Plant (WWTP) only treats domestic wastewater from a few sub-districts in Jambi City. Therefore, it is necessary to expand the service area through development design to increase sewerage treatment quality and reduce the possibility of water pollution in Jambi City. This research was conducted in Talang Banjar Sub-district, Jambi Timur District and based on the Regulation of the Ministry of Public Works and Housing Number 4 of 2017.  The result shows that in 2045, there would be 10,760 people and 418 units of public facilities that produce domestic wastewater in Talang Banjar Sub-district. The amount of domestic wastewater discharge is 19.506 l/s. The sewer line length is 9897.7 meters and the pipe excavation depth ranges from 0.84 to 11.86 meters. The pipe material used is PVC SDR 41 with diameter ranges from 110 to 200 mm. The sewer appurtenances consists of 191 manholes, 37 clean outs, 4 drop manholes and 4 wet-wells. The sewer line construction is expected to cost Rp42.392.529,00. This design must be evaluated in order to make it more cost-effective and technically efficient.